1995
DOI: 10.1002/cne.903560103
|View full text |Cite
|
Sign up to set email alerts
|

Zonal organization of the climbing fiber projection to the flocculus and nodulus of the rabbit: A combined axonal tracing and acetylcholinesterase histochemical study

Abstract: The localization and termination of olivocerebellar fibers in the flocculus and nodulus of the rabbit were studied with anterograde axonal transport methods [wheatgerm agglutinin-horseradish peroxidase (WGA-HRP) and tritiated leucine] and correlated with the compartments in the white matter of these lobules delineated with acetylcholinesterase histochemistry (Tan et al. J. Comp. Neurol., 1995, this issue). Olivocerebellar fibers originating from the caudal dorsal cap travel through floccular compartments FC2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 94 publications
10
70
1
Order By: Relevance
“…There is anatomical evidence that suggests that the region of the calretinin area is reciprocally connected with the cerebellum, and specifically the nodulus (Sato et al 1983;Langer et al 1985b;Shojaku et al 1987;Walberg and Dietrichs 1988;Epema et al 1990;Barmack et al 1992c;Tan and Gerrits 1992;Tan et al 1995;Xiong and Matsushita 2000). The notion that the calretinin-immunoreactive cells themselves project to the cerebellum is consistent with the finding of a cholinergic projection from the VNC to the cerebellum (Barmack et al 1992a(Barmack et al , 1992c.…”
Section: Functional Considerationssupporting
confidence: 73%
See 1 more Smart Citation
“…There is anatomical evidence that suggests that the region of the calretinin area is reciprocally connected with the cerebellum, and specifically the nodulus (Sato et al 1983;Langer et al 1985b;Shojaku et al 1987;Walberg and Dietrichs 1988;Epema et al 1990;Barmack et al 1992c;Tan and Gerrits 1992;Tan et al 1995;Xiong and Matsushita 2000). The notion that the calretinin-immunoreactive cells themselves project to the cerebellum is consistent with the finding of a cholinergic projection from the VNC to the cerebellum (Barmack et al 1992a(Barmack et al , 1992c.…”
Section: Functional Considerationssupporting
confidence: 73%
“…That study found that the region at the border of PH and VMN, the site of our dense patch of calbindin-labeled fibers, was free of calbindin-labeled fibers in those animals. Several studies suggest the most likely source of cerebellar projections to the regions of dense calbindin fiber label is the flocculus (Sato et al 1982;Langer et al 1985a;Shojaku et al 1987;Umetani 1992;De Zeeuw et al 1994;Tan et al 1995). The calbindin-dense patches thus define input compartments.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Cerebellar zones containing rVA cells receive input from the caudal dorsal cap, whereas r45 c cells receive input from the rostral dorsal cap and ventrolateral outgrowth. 2,16,23 Nonetheless, in the present study, we found no appreciable differences in the location of retrograde labeling in the IO following injections at locations containing rVA vs r45 c cells. Likewise, we found no obvious differences in the locations of retrogradely labeled cells following injections in areas of the translation zone at locations containing different response types.…”
Section: Discussioncontrasting
confidence: 48%
“…2,16,23 Barmack et al 3,4,5 have shown that many neurons in this zone and the beta subnucleus respond to static head tilt, thus demonstrating an input originating in the otolith organs. Although not self-translation per se, the medial zone of the nodulus/uvula and the beta subnucleus in rabbits receive inputs related to linear acceleration during self-motion, as does the medial VbC in pigeons.…”
Section: Comparative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation